(untitled) (Journal of Asian Development Studies, 2024)
This study search into the critical features of classroom management techniques and their impact on students’ effective learning at public primary school level in district Sangahar Sindh. Effective classroom management is a base to lead high quality learning environment to assist student engagement that grow academic achievement. The research work to survey the present condition of classroom management implementation in public primary schools in district Sanghar analyze their impact on students learning outcome. This research employs a quantitative approach and analysis methods. A survey questions was conduct from primary school teachers in district Sanghar to collect data on their classroom management practices. The outcomes of this study analyze the most frequently used classroom management techniques by primary school teachers in district Sanghar examining the impact of these techniques on students’ academic achievement, engagement, behavior and analyze the relationship between classroom management practices and student learning outcome. The findings will be prepared precious awareness for teachers, policy makers, and education collaborator to make better classroom management process increase student learning and assist academic excellence in district Sanghar. The impact of classroom management techniques on students’ effective learning has significant relationship towards the development of active body of knowledge and result suggested authentication about these practices that support student success in all manners.